PERENCANAAN PRODUKSI AGREGAT BERDASARKAN PENDEKATAN OPTIMASI PROGRAMA LINIER DI PERUSAHAAN SEPATU OLAH RAGA - Sulistyadi, Kohar; Saputro, Firdhaus Hari; Himawan, Pandu (JURNAL GAUNG INFORMATIKA, 2013)
Effort to minimize the cost of production companies in an effort to increase competitive advantage through a number of ways to implement strategies to meet theminimum production costs demand. In this research is focused on aggregate production planning through several stages, namely: (1) forecasting product demand in the coming year, (2) aggregate production planning with reference to "equal demand and supply" at a minimal cost. Many methods in the aggregate production planning for the use of linear programming based optimization approach to obtain the optimal value with minimal cost. The final results of the linear programming optimization approach based on the  lowest available cost of U.S. $. 57,178,349. for a number of sports shoes demand 6,609,634 pieces